2013
DOI: 10.1016/j.langcom.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

How to do things with slurs: Studies in the way of derogatory words

Abstract: Croom, A. M. (2013). How to do things with slurs: Studies in the way of derogatory words. Language and Communication, 33, http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 91 publications
(116 reference statements)
1
71
0
4
Order By: Relevance
“…Jay (2009) has pointed out, for example, that prohibitions on taboo words are often reinforced during child-rearing practices. In several studies focusing on slurs, Croom (2011Croom ( , 2013 has further suggested that descriptive expressions like male and female are commonly used and understood to be most apt for neutrally picking out public items of the shared inter-subjective or objective world, that expressive expressions like fuck and yikes are commonly used and understood to be most apt for expressing one's own heightened (positive or negative) emotional state, and that slur expressions like slut and chink are commonly used and understood to be most apt for typically targeting certain members on the basis of their descriptive attributes (such as their race or sex) in order to derogate, offend, or disassociate (or in cases of appropriation, affiliate) with them on this basis (Croom, 2008, p. 38-45;Croom, 2011, p. 349-353). That is to say, language-users that have developed a facility or attunement to the use-conditions for slur expressions will typically expect that their use will correlate with the speaker being in a heightened derogatory or discriminatory state toward some target member (or wishing to create that impression), and accordingly, that speakers will only use slurs when they are in a heightened derogatory or discriminatory state toward some target member (or wishing to create that impression).…”
Section: Face Threating Acts and The Paradigmatic Derogatory Use Of Smentioning
confidence: 99%
See 4 more Smart Citations
“…Jay (2009) has pointed out, for example, that prohibitions on taboo words are often reinforced during child-rearing practices. In several studies focusing on slurs, Croom (2011Croom ( , 2013 has further suggested that descriptive expressions like male and female are commonly used and understood to be most apt for neutrally picking out public items of the shared inter-subjective or objective world, that expressive expressions like fuck and yikes are commonly used and understood to be most apt for expressing one's own heightened (positive or negative) emotional state, and that slur expressions like slut and chink are commonly used and understood to be most apt for typically targeting certain members on the basis of their descriptive attributes (such as their race or sex) in order to derogate, offend, or disassociate (or in cases of appropriation, affiliate) with them on this basis (Croom, 2008, p. 38-45;Croom, 2011, p. 349-353). That is to say, language-users that have developed a facility or attunement to the use-conditions for slur expressions will typically expect that their use will correlate with the speaker being in a heightened derogatory or discriminatory state toward some target member (or wishing to create that impression), and accordingly, that speakers will only use slurs when they are in a heightened derogatory or discriminatory state toward some target member (or wishing to create that impression).…”
Section: Face Threating Acts and The Paradigmatic Derogatory Use Of Smentioning
confidence: 99%
“…4 Cf. adequacy condition 2 of 6 on p. 355 in Croom (2011) and adequacy condition 2 of 7 on p. 200 in Croom (2013). Note also that although the expressions property and feature are often used in the extant literature to identify that which can be ascribed to individuals (for example, race, sex, and so on), here I try to use the expression attribute instead since it does not seem to suggest as strongly that what is being ascribed to these individuals is something that the individual is actually endowed with.…”
mentioning
confidence: 98%
See 3 more Smart Citations